Rancang Bangun Sistem Kamera Pengawas Pendeteksi Gerakan Menggunakan Metode Background Subtraction Berbasis Raspberry Pi - Kusumawardhani, Febrianty Dwi; Fahruzi, Akhmad (INTEGER: Journal of Information Technology, 2023)
In this complicated era, the crime rate, such as that of targeting an empty house, is on the rise. Empty houses are indeed quite vulnerable to becoming targets for the criminals that are now rampant, especially in big cities. Preventions such as installing CCTV at home are deemed necessary, despite the fact that they do not guarantee the complete security of the homes in which people live. CCTV monitoring systems usually use a computer and TV monitors that are connected to their local network, thereby making the system less effective when the location or room is being left by the owner because it cannot be monitored directly. This study designed a surveillance camera using a Raspberry Pi and Camera Pi NoIR that can detect movement and is equipped with notifications when movement is detected so that the home monitoring system becomes more efficient even though the homeowner is away. The method employed for motion detection was the background subtraction method, while the notification was via Telegram bot messages. The tool design has passed several tests, namely testing based on threshold values, testing sensitivity at a distance, and testing sending notifications from Telegram bots. It gained accuracy in motion detection by 83.33%. Overall, the system was running well, as expected.Keywords: motion detector, Raspberry Pi, Pi NoIR camera, background subtraction, telegram